Responses of fine-root biomass and production to drying depend on wetness and site nutrient regime in boreal forested peatland - Lampela, Maija; Minkkinen, Kari; Straková, Petra; Bhuiyan, Rabbil; He, Wei; Mäkiranta, Päivi; Ojanen, Paavo; Penttilä, Timo; Laiho, Raija (Frontiers in Forests and Global Change, 2023)
Introduction Peatlands are terrestrial-carbon hotspots, where changes in carbon pools and fluxes potentially caused by drying or warming may have significant feedbacks to climate change. In forested peatlands, fine-root biomass (FRB), and production (FRP) are important carbon pools and fluxes, but they and their depth distribution and plant functional type (PFT) composition are poorly known. Methods We studied the effects of persistent water-table level (WTL) drawdown on these characteristics in four forested boreal peatland site types that varied in soil nutrient and WTL regimes, ground vegetation and tree stand characteristics. Each site type was represented by a pair of one undrained and one drained site. Two pairs were nutrient-poor, Scots pine dominated sites, one very wet and one relatively dry in their undrained condition. The other two pairs were nutrient-rich, Norway spruce dominated sites, again one wetter and one drier in the undrained condition. FRB was estimated by separating and visually identifying roots from soil cores extending down to 50 cm depth. FRP was estimated using ingrowth cores covering the same depth, and the separated roots were identified using infrared spectroscopy. Results and discussion Both FRB and FRP varied widely both within and among the different types of boreal forested peatland. In FRB, the clearest differences were seen in the two originally wettest sites, nutrient-poor tall-sedge pine fen and nutrient-rich herb-rich spruce swamp: FRB was smaller in the drained site compared to the undrained site in the pine fen, but the opposite was true in the spruce swamp. FRP was generally higher in the nutrient-poor, pine-dominated sites than the nutrient-rich, spruce-dominates sites. The depth distribution of FRB was more superficial than that of FRP, except for the most nutrient-rich spruce swamp. Tree and shrub roots dominated both FRB and FRP, except for the undrained pine fen, where graminoids and forbs dominated. Even there, these PFTs were replaced by trees and shrubs at the drained site. Site wetness and nutrient regime both thus clearly regulated FRB and FRP of the forested peatland site types studied, and both need to be considered when making any generalizations.